BUYING AND BUYING IMPORTED USED CLOTHING ACCORDING TO SYAFI'IIYAH AND TRADE LAW NO 7 OF 2014 - Nazaruddin, Nizar; Wangsa, Danu (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
This research discusses a review of the buying and selling of imported used clothing from the perspective of the Imam Syafi'i School and Trade Law no. 7 of 2014, with a case study on the Slugstore Imported Used Clothing Store. The aim of this research is to analyze the suitability of the practice of buying and selling imported used clothing with the principles of Islamic law and trade regulations applicable in Indonesia. This research uses a qualitative method with a case study approach. Data collection techniques were carried out through interviews, observation and documentation studies. The research results show that from the perspective of the Imam Syafi'i School, buying and selling used clothes is permitted as long as the goods are clean, do not contain impurities, and do not cause harm to the buyer. However, based on Article 47 of Trade Law no. 7 of 2014, trade in imported used clothing is prohibited because it is considered to have the potential to harm domestic industry and have a negative impact on public health. The results of this research show that there are differences in views between Islamic law and state regulations regarding the trade in imported second-hand clothing. Therefore, a solution is needed that is able to accommodate sharia principles while supporting national trade policies.